Mineral prospectivity analysis of the Wagga-Omeo belt in NSW - Robson, David; Mamuse, Antony; Guj, Pietro (Taylor & Francis, 2021)
The Wagga-Omeo Belt in NSW has been a significant tin, gold, silver and copper producer. An analysis of the mineral prospectivity of the region has been undertaken by estimating the number of undiscovered deposits, estimating mineral endowment, and by predicting the likely locations of undiscovered deposits. Both spatial prediction (mineral prospectivity mapping - MPM) and quantitative resource assessment (QRA) were undertaken with a focus on tin mineralisation in the region.